1994
DOI: 10.1007/bf01347711
|View full text |Cite
|
Sign up to set email alerts
|

Growth, biomass allocation and water use efficiency of two wheat cultivars in a mediterranean environment; a pot experiment under field conditions

Abstract: Plants of two bread wheat cultivars, Triticum aestivum L. 'Katya AI' and 'Mexipak 65', were grown in pots during the crop season in the field in NW Syria, a region with a Mediterranean climate. The experiment involved two treatments. Control plants were well-watered throughout the experiment (watering to 0.22 g water g-1 dry soil). In the second treatment, water was withheld from the plants until soil water content had decreased to 0.10 g water g-1 dry soil, the level that was maintained thereafter. Water use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 8 publications
2
13
0
Order By: Relevance
“…). In high‐yielding wheat genotypes, for instance, drought resulted in partitioning of a greater proportion of dry weight in stems instead of both leaves and roots (Veneklaas and Peacock ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…). In high‐yielding wheat genotypes, for instance, drought resulted in partitioning of a greater proportion of dry weight in stems instead of both leaves and roots (Veneklaas and Peacock ).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that genotypes may vary strongly in biomass partitioning to the different organs under drought conditions (Asch et al 1999). In high-yielding wheat genotypes, for instance, drought resulted in partitioning of a greater proportion of dry weight in stems instead of both leaves and roots (Veneklaas and Peacock 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in plant water use efficiency are related to differences in the ratio of photosynthesis and transpiration for potgrown wheat cultivars (Condon et al, 1990;Farquhar and Richards, 1984;Veneklaas and Peacock, 1994). The ratio of the photosynthetic rate and transpiration rate of the leaf has a major influence on plant water use efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The photosynthesis measurements summarized in Table 1 were carried out under standardized conditions, so actual rates may differ as a result of different illumination, temperature etc. Results from a previous study (Veneklaas & Peacock, 1994) suggest tbat differences in respiration may account for differences in conversion of assimilates to biomass. Mexipak had 9 "o lower WUE^ but only 4% lower WUE^.…”
Section: Cjas Exchangementioning
confidence: 87%